Multi-Omics Analyses Uncover the Mechanism Underlying Polyploidization-Enhanced Steviol Glycosides Biosynthesis in Stevia rebaudiana - Juan Liu; Jiaxue Wang; Mingjia Chen; Wenna Meng; Anping Ding; Miao Chen; Rongping Ding; Mingpu Tan; Zengxu Xiang (Plants)
Stevia rebaudiana (Bertoni) is a valuable sweetener plant whose sweetness primarily derives from steviol glycosides (SGs), especially rebaudioside A (RA). Polyploidization has the potential to enhance the content of active ingredients in medicinal plants, making this strategy a promising avenue for genetic improvement. However, the underlying regulatory mechanisms that contribute to the fluctuating SGs content between autotetraploid and diploid stevia remain unclear. In this study, we employed metabolic analysis to identify 916 differentially accumulated metabolites (DAMs), with the majority, specifically terpenoids, flavonoids, and lipids, exhibiting upregulation due to polyploidization. Notably, the content of stevia’s signature metabolite SGs (including RA, steviolbioside, and rebaudioside C), along with their precursor steviol, increased significantly after polyploidization. Furthermore, a comprehensive analysis of the transcriptome and metabolome revealed that the majority of differentially expressed genes (DEGs) involved in the SG-synthesis pathway (ent-KAH, ent-KS1, UGT73E1, UGT74G1, UGT76G1, UGT85C2, and UGT91D2) were upregulated in autotetraploid stevia, and these DEGs exhibited a positive correlation with the polyploidization-enhanced SGs. Additionally, multi-omics network analysis indicated that several transcription factor families (such as five NACs, four WRKYs, three MYBs, eight bHLHs, and three AP2/ERFs), various transporter genes (four ABC transporters, three triose-phosphate transporters, and two sugar efflux transporters for intercellular exchange), as well as microorganisms (including Ceratobasidium and Flavobacterium) were positively correlated with the accumulation of RA and steviol. Overall, our results indicate the presence of a regulatory circuit orchestrated by polyploidization, which recruits beneficial rhizosphere microbes and modulates the expression of genes associated with SG biosynthesis, ultimately enhancing the SG content in stevia. This finding will provide new insights for promoting the propagation and industrial development of stevia.